Effect of Alexithymia on Internet Addiction Among College Students: The Mediating Role of Metacognition Beliefs - Luo, Hongge; Zhao, Yanli; Hong, Jiangyue; Wang, Hong; Zhang, Xiujun; Tan, Shuping (Frontiers in Psychology, 2022)
Background: Previous studies have found that alexithymia plays an important role in the pathogenesis of Internet addiction. However, the effect of alexithymia on both metacognition and Internet addiction has yet to be examined. Methods: The Toronto Alexithymia Scale, Metacognition Questionnaire, and Internet Addiction Test were assessed in a sample of 356 college students. A parallel mediator effect analysis was used to test the hypothesis that metacognition mediates the relationship between alexithymia and Internet addiction. Results: The parallel multiple mediator model showed that alexithymia predicted the five dimensions of metacognition and Internet addiction, and that three dimensions–cognitive confidence, positive beliefs about worry, and the need to control thoughts partially mediated this relationship. Conclusion: Alexithymia could directly and indirectly predict Internet addiction via metacognition.